Causality Analysis Between Collaboration Profiles and Musical Success - Silva, Mariana O.; Moro, Mirella M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Current research in music collaboration networks has established that social interaction can impact the music industry’s trajectory. In a previous study, we found that the way artists connect professionally may affect their musical success. Subsequently, our goal is to deepen such analyses by using time series and Granger causality test for assessing whether there is a causal relationship between collaboration profiles and artist’s popularity. Our experimental evaluation reveals varied relationships linking collaboration profiles and musical success, indicating a direct connection between these two factors analyzed.